العوامل الثّقافية وتأثيرها على سلوك المستهلك تجاه الإعلان عبر الإنترنت دراسة مسحية في الساحل السوري - غدير باسم غدير; اسماعيل هبه محمد (Latakia University Journal - Economic and Legal Sciences Series, 2016)
مع التطوّر الكبير في تكنولوجيا المعلومات والاتصالات، وانتشار الإنترنت بشكل واسع في جميع أنحاء العالم. اتجهت منظمات الأعمال إلى بيئة العمل الإلكترونية، ونلاحظ أنّ سورية تحاول مواكبة هذا التطور ودخول بيئة العمل الإلكترونية، من خلال استخدام منظمات الأعمال لهذه البيئة في الترويج لأعمالها ومنتجاتها، ومن عناصر الترويج التي تم استخدامها من قبل هذه المنظمات كان الإعلان عبر الإنترنت. ولكن يختلف تأثير هذا الإعلان باختلاف ثقافة كل بلد، والمستهلكين الذين يرون هذا الإعلان؛ لما تملكه العوامل الثقافية من تأثير كبير على سلوك المستهلك بشكل عام. لذلك فإنّ هذا البحث يهدف إلى دراسة مدى تأثير هذه العوامل الثقافية على سلوك المستهلك تجاه الإعلان عبر الإنترنت ومدى قبوله لهذه التقنيات الحديثة، من خلال دراسة مسحية لعيّنة من المستهلكين في الساحل السوري تم فيها توزيع 209 استبانات. ومن أهم النتائج التي تم التوصل إليها أنّ الإعلان عبر الإنترنت لا يتفق مع القيم والعادات التي يحملها المستهلكون، كما أنّ المستهلكين يفضلون مشاهدة الإعلان عبر الإنترنت باللّغة التي يتحدثون بها. With the great development of communication and information technology, and the net spread extensively all over the world. Works’ organizations went towards electronic work environment, and we notice that Syria is trying to keep up with this development and entering electronic work environment by using works’ organizations this environment in spreading their works and products, and of spreading elements which has been used by these organizations was the online advertising. But the effect of this advertising differs by differing of culture of each country and consumers who see this advertising, for what the cultural factors have of great effect on the consumer’s behaviour generally. So this research aims to study the effect of these cultural factors on the consumer’s behaviour towards online advertising and his acceptance the modern technology buy survey study to a group of consumers in the Syrian coast in which they distributed 209 questionnaires. One of the most important results which has been achieved is that the online advertising doesn’t agree with value and habits which consumer have, also consumers prefer watching online advertising with the language which they speak with.